Framing Static and Dynamic Time-Periods through the Teleological Lens in the Implementation Process of Enterprise Resource Planning. Issue 4 (2nd October 2021) - Rodríguez, Rocío; Otero-Neira, Carmen; Svensson, Göran
ABSTRACT: Purpose: Enterprise Resource Planning (ERP) is a technological tool which improves and eases B to B communication and reinforces business relationships as well as business-to-business ( B to B) marketing . Based on a teleological lens in B to B relationships between ERP sellers and ERP buyers, the research objective of this study is to frame static and dynamic time-frames in the ERP implementation process in B to B markets. The aim is to shed light on the consideration of time-periods (i.e. past, present and future) as either tatic or dynamic in the implementation process of complex service solutions, such as ERP, in a B to B marketing setting. Design/methodology/approach: This study is conducted with respect to Spanish companies focusing on the first main pre-implementation, first main implementation and first main post-implementation process of ERP software solutions in B to B markets . This study embraces a multi-method design consisting of the four phases. It enables data triangulation through in-depth structured interviews in a follow-up study, so as to validate the results. Findings: Reports static and dynamic time-periods through a teleological lens in the implementation process of ERP in B to B market of the Spanish healthcare industry. This study indicates that more than half of the ERP buyers were not entirely satisfied, after finalizing the ERP implementation process. Subsequently, less than half of them received only a software solution and the rest considered they had received merely a somewhat adapted software solution. Furthermore, only one out of ten confirmed that the software solution obtained was a fully adapted solution beyond the ERP buyers' expectations and truly taking into account their needs. This study also reveals that there are still some ERP implementation processes indicating that the seller does not take into account the needs of the buyer at all. Altogether, the findings indicate that the B to B marketing process is often not satisfactory. It is widely known that the ERP is a standardized tool that requires adaptation of the ERP software solution to the buyer' in B to B markets. Research limitations/implications: The combination of static and dynamic considerations of time with formative, rationalist and transformative teleological lenses outline and distinguish between various strategies for handling the ERP pre-implementation process, the ERP implementation process and the ERP post-implementation process in B to B marketing. We contend that another core research implication in B to B marketing, taking into consideration static and dynamic time-periods through the teleological lens, addresses the need to match the ERP seller perspective with that of the ERP buyer. A mismatch may turn out unsatisfactorily for both the ERP seller and the ERP buyer. It is therefore crucial in the B to B marketing strategy that there be a balance between flexibility and adaptations of the ERP seller to the expectations and experiences of the ERP buyer in the ERP implementation processes in B to B markets. Managerial implications: O ffers opportunities for companies to apply B to B marketing strategies through visualizing in advance the cost and risk associated with an ERP implementation. Furthermore, this study enables the framing of other complex service implementation processes such as the ERP software solution. A core managerial implication of the results reported in this study to B to B marketing is the need to distinguish between static and dynamic, using the time-periods in the ERP implementation. The ERP seller needs to align its strategy of B to B marketing with its consequences from the ERP pre- and post-implementation processes. Another core managerial implication is that the static and formative use of time entails less costs initially. It enables the ERP seller to obtain benefits within a short time-frame. However, the ERP seller may have to face a dissatisfied ERP buyer at the end of the implementation process. Subsequently, the risk of the relationship disruption is high, so that this strategy of B to B marketing has a short-time orientation, based on targeting many ERP buyers and devoting less effort to each of them (by the ERP seller). In the case of the dynamic and rationalist use of time-periods, the ERP seller has chosen a strategy of B to B marketing with the ERP buyer that can turn out satisfactorily. However, the initial costs are higher than when the static consideration of time is used because the ERP seller needs more resources, expertise and skills to visualize the end of the implementation process taking into account the actual requirements. Originality/value: F rames static and dynamic time-periods which influence the B to B marketing strategy used in the implementation process of ERP in the healthcare industry. The teleological lens applied in this study contributes to contextualizing as marketing B to B tool the ERP implementation process as being either past-based (formative), present-based (transformative) or future-based (rationalist).